Analysis of the Application of Problem Based Learning Model to Students’ Problem Solving Skills on the Material of the Stages of Foundation Work Implementation in SMK - Good Meicel Mendrofa; Envilwan Berkat Harefa; Aprianus Telaumbanua; Arisman Telaumbanua (Edumaspul: Jurnal Pendidikan, 2024)
The problem in this study is that students‘ problem solving skills are still lacking, marked by students’ difficulty in analysing problems in depth before trying to solve them, due to the lack of opportunities for students to solve problems regularly and resulting in students not having sufficient skills. The purpose of the study was to analyse the application of the Problem Based Learning model to students' problem solving skills in vocational schools. The type of research is experimental research. This research was conducted at SMK Negeri 1 Hiliserangkai. The research population was all students of class XI-BKP SMK Negeri 1 Hiliserangkai in the 2023/2024 academic year consisting of 2 classes. This study used a randomised pretest posttest experiment control group design. The research instrument was a problem solving ability test in the form of a description test. Before being determined as a research instrument, the test was validated to the building engineering vocational teacher and tested at SMK Negeri 1 Botomuzoi for the purpose of testing the feasibility of the test. Research results: 1) The average result of students' problem solving ability using the Problem Based Learning learning model is 77.83 classified as good; 2) The average result of students' problem solving ability using the conventional model is 68.25 classified as sufficient; 3) The results of hypothesis testing obtained tcount = 2.23 and ttable = 2.001. Because thitung does not lie in the interval - ttabel ≤ t ≤ ttabel. So the hypothesis that reads: ‘there is a significant effect of the Problem Based Learning model on students‘ problem solving skills on the material of the stages of foundation work implementation at SMK Negeri 1 Hiliserangkai.’ accepted at the 95% confidence level or 5% significant level (α=0.05). Researchers suggest that teachers should apply the Problem Based Learning model in learning, especially to present vocational material such as the stages of foundation work implementation.